Improving teaching effectiveness through transformational leadership and integrity - Masduki Ahmad; Heni Rochimah (International Journal of Evaluation and Research in Education (IJERE), 2021)
The study aimed to determine the impact of transformational leadership and integrity on the performance of a company. The research sample was 123 lecturers at As-Syafi’iyah Islamic University, Indonesia. The analysis model of this study was a path analysis. Observation and questionnaires were used to obtain the research data. Teaching effectiveness measures how well educators' instruction aligns with learning objectives and provides the best possible outcomes for students who are taking the course. Hypothesis testing was performed using the t-test. The SPSS software version 25 was applied in statistical calculations. The results showed that transformational leadership and integrity have direct and positive impact on the teaching effectiveness. Transformational leadership has a direct and positive impact on the integrity. It is suggested to implement the better transformational leadership to achieve the better the teaching effectiveness.